Enhancing Communication Skills In English Through Neuro Linguistic Programming: A Study (Journal of Namibian Studies : History Politics Culture, 2023)
Neuro-Linguistic Programming (NLP) is an interpersonal communication system, developed by John Grinder, an associate professor of linguistics, and Richard Bandler, a mathematician and a graduate student of psychology, in the early 1970s as a new method to language teaching. It is a collection of strategies, techniques, and patterns which are used for effective communication, growth, and personal change. The originators of NLP studied different patterns of beliefs and subjective experiences of the people with excellent behaviour (Revell & Norman, 1997) in order to discover the structures of excellence. As they believe that all behaviours have some structures, and by discovering the excellent patterns and modelling them, it is possible to repeat the same patterns and gain the same favourable results.